Enhanced magnetic properties of polymer-magnetic nanostructures synthesized by ultrasonication - Thanigai Arul, K.; Manikandan, E.; Marmu, P.P.; Kennedy, J.; Henini, M. (Elsevier, 2017)
Polymer based nickel (Ni) and cobalt (Co) co-doped ferrites were prepared by adept ultrasonication route. Different concentrations of polymer [polyvinyl alcohol (PVA)] (0.2 g and 0.5 g) was added as a surfactant to the magnetic particles. The phase purity of Ni-Co ferrites (spinel structure) was confirmed by X-ray diffraction (XRD). Enhanced saturation magnetization of polymer based magnetic nanoparticles due to shape anisotropy and size. 0.2 wt% doped ferrite showed superparamagnetic characteristics with blocking temperature above room temperature. Hence, ultrasonication route is a rapid and effective technique for tailoring size and morphology of magnetic nanostructure that could be useful in magnetic-sensor applications.